Tibial reconstruction using a non-vascularised fibular transfer - Morsi, Elsayed (Springer-Verlag, 2002)
A non-vascularised contralateral fibular transfer was performed on seven patients with non-union of the tibia and a sclerosed segmental bone defect following injury. The average follow-up was 2.7 years with a minimum of 2 years. The operation was successful in achieving fracture union in six patients, with an average time to union of 4.5 months (range: 3–6). Shortening of up to 2.4 cm was found in two patients and mild residual ankle stiffness in one. This procedure is successful and simple when compared to microvascular and Ilizarov techniques.